Cyberspace: The “Color Line” of the 21st Century - Molina, Alejandro (Social justice, 2003)
Part of a special issue on war, dissent, and justice from the perspective of scholars, activists, and former U.S. political prisoners. The militaristic and intrusive direction being taken by information technology has huge potential for abuse, and the struggle for human rights is interconnected with cyberspace. Information technology is increasingly being appropriated by the military and prison system and could be used in the future to provide a checkbox for political association, affiliation, and organization. However, cyberspace can also be used by activists to internationalize their struggles and to expand knowledge about their strategies.